A computational fluid dynamics analysis of cryo-CO2 flow and thermal behaviour in high-speed milling process - Nur Fatini, Mohamad Fauzee; Nurul Hayati, Abdul Halim; Zainoor Hailmee, Solihin; Izdihar, Tharazi; Irnie Azlin, Zakaria; Musfirah, Abdul Hadi (Elsevier Ltd, 2025)
Cryogenic CO2 machining performance is mainly dependent on how well heat generated during cutting is dissipated from the cutting zone. Understanding the heat transfer phenomenon is crucial for optimizing thermal behavior and its effects, which remain challenging to capture experimentally. Thus, this novel study aimed to optimize the thermal behaviour of the cutting tool and workpiece of high-speed milling under cryo-CO2 cooling by the combination of computational fluid dynamics (CFD) analysis and RSM-Box Behnken design. A complex 3D cryo-CO2 model was developed and validated against experimental data of cryo-CO2 flow temperature and it showed differences of less than 6 % when compared with CFD results. By the RSM-BBD method, 15 sets of parameters were simulated where the influence of cryo-CO2 flow rate, nozzle distance (D), and nozzle diameter (∅) on heat transfer coefficients (h) and heat transfer rates (Q) were analyzed through ANOVA. The simulations resulted in h ranging from 33.75 W/m2 to 88.92 W/m2 and Q of between 126.22 W to 301.25 W. Cryo-CO2 temperature trajectory and splashing effect from the nozzle to the cutting zone were also observed. The proportion of the h had a significant influence on the heat transfer. Further studies on tool and workpiece surface temperatures were conducted, where a higher flow rate had been suggested for advanced heat dissipation. ANOVA revealed both responses were dominantly influenced by flow rate followed by nozzle distance and their interaction. By multi-objective optimization, an optimum set of parameters was identified: flow rate = 13 L/min, D = 15 mm; ∅ = 1.3 mm and predicted to produce h at 77.23 W/m2 and Q at 264.45 W for maximum heat dissipation. Thus, it is worth mentioning that this study provided some potential approaches and a promising way for the enhancement of cryo-CO2 system towards optimizing the efficiency and performance of cryo-CO2 machining.